A Non-Parametric Analogy between Oracle & MySQL: Syeda Binish Zahra - Syed, Syed Muhammad Shabih-ul-Hassan; Syed, Syeda Binish Zahra1; Sadia Kuasar, Sadia Kuasar; SUNDUS MUNIR, SUNDUS MUNIR; Afrozah Nadeem5, Afrozah Nadeem (International Journal for Electronic Crime Investigation, 2020)
Database Servers store, manipulate and retrieve critical information. In current computing era these database servers are often exercise unauthorized access, security breaches and violation. A sub field of digital forensic called Database Forensic deals with the study of database and about their data. Oracle server and SQL Server are two database server actively used by digital industry for their data store. This research paper is a detailed non parametric comparison between oracle server and SQL Server that helps forensic investigators in DB tool selection for the sake of forensic analysis and investigation of databases. According to findings oracle is more secure than SQL, oracle data types are more flexible than SQL. Both tools are good at query optimization but oracle is more expensive than SQL. This comparison is made with the expectation of escalating research in database forensic analysis and investigation areas.